2013
DOI: 10.1016/j.pain.2013.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The Pain Course : A randomised controlled trial of a clinician-guided Internet-delivered cognitive behaviour therapy program for managing chronic pain and emotional well-being

Abstract: The present study evaluated the efficacy of a clinician-guided Internet-delivered cognitive behaviour therapy (iCBT) program, the Pain Course, to reduce disability, anxiety, and depression associated with chronic pain. Sixty-three adults with chronic pain were randomised to either a Treatment Group or waitlist Control Group. Treatment consisted of 5 iCBT-based lessons, homework tasks, additional resources, weekly e-mail or telephone contact from a Clinical Psychologist, and automated e-mails. Twenty-nine of 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
213
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(231 citation statements)
references
References 36 publications
15
213
0
3
Order By: Relevance
“…Several recent clinical trials implemented self-referral as a recruitment option. 20,28,43,44 In addition, the privacy and anonymity of Internet-delivered CBT may help patients who are introverted or depressed to be more open and receptive to treatment. 7 From a clinical efficiency perspective, Internetdelivered CBT offers substantial benefits.…”
Section: What Are the Advantages Of Internet-delivered Cbt Over Face-mentioning
confidence: 99%
“…Several recent clinical trials implemented self-referral as a recruitment option. 20,28,43,44 In addition, the privacy and anonymity of Internet-delivered CBT may help patients who are introverted or depressed to be more open and receptive to treatment. 7 From a clinical efficiency perspective, Internetdelivered CBT offers substantial benefits.…”
Section: What Are the Advantages Of Internet-delivered Cbt Over Face-mentioning
confidence: 99%
“…Australia (Dear et al, 2013;Nicholas et al, 2011;Chen & Francis, 2010) and the Netherlands (Samwel et al, 2009). In many of these studies, some of the participants were immigrants.…”
Section: Participantsmentioning
confidence: 99%
“…Of the 17 studies analysed, six were experimental studies -randomised control trials (Poleshuck et al, 2014;McCracken, Sato & Taylor, 2013;Tse, Vong & Tang, 2013;Dear et al, 2013;Frich et al, 2012;Chen & Francis, 2010) and eleven were pseudo-randomised trials (Fullen et al, 2013;Lattie et al, 2013;Nash et al, 2013;Taloyan, Alinaghizadeh & Löfvander, 2013;Tan et al, 2013;Nicholas et al, 2011;Bremander, Holmström & Bergman, 2010;Darchuk et al, 2010;Samwel et al, 2009;Unützer et al, 2008;Field et al, 2007). Based on our methodological quality instruments, we concluded that all the studies presented a high level of evidence.…”
mentioning
confidence: 95%
“…Meta-analyses of iCBT for depression in the general population have demonstrated moderate to large effect sizes that provide evidence that iCBT is comparable to face-to-face CBT (23)(24)(25). Furthermore, specific benefits of iCBT for pain-related conditions have been reported (26,27). These factors suggest that iCBT may be particularly well-suited to older OA patients, particularly those with diminished mobility, and this form of intervention is aligned with the greater call for more accessible and flexible care pathways for arthritis (22).…”
Section: Introductionmentioning
confidence: 99%